2018
DOI: 10.1136/jech-2017-210328
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autonomy, job demands and working hours after diagnosis of chronic disease: a comparison of employed and self-employed older persons using the English Longitudinal Study of Ageing (ELSA)

Abstract: BackgroundModifications in working conditions can accommodate changing needs of chronically ill persons. The self-employed may have more possibilities than employees to modify their working conditions. We investigate how working conditions change following diagnosis of chronic disease for employed and self-employed older persons.MethodsWe used waves 2–7 from the English Longitudinal Study of Ageing (ELSA). We included 1389 participants aged 50–60 years who reported no chronic disease at baseline. Using fixed-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Interestingly, the autonomy wielded by entrepreneurs that may drive the loss of recovery may also be the key to successful interventions in the entrepreneurship context. For example, entrepreneurs reduced their working hours by approximately 3 hr after receiving a diagnosis of chronic disease (e.g., congestive heart failure, lung disease), while employees did not and possibly could not (Fleischmann et al, 2018). Scholars would make important progress toward addressing entrepreneurial ill-being by co-designing and marketing interventions among entrepreneurial samples to combat the inability to recover while encountering considerable stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the autonomy wielded by entrepreneurs that may drive the loss of recovery may also be the key to successful interventions in the entrepreneurship context. For example, entrepreneurs reduced their working hours by approximately 3 hr after receiving a diagnosis of chronic disease (e.g., congestive heart failure, lung disease), while employees did not and possibly could not (Fleischmann et al, 2018). Scholars would make important progress toward addressing entrepreneurial ill-being by co-designing and marketing interventions among entrepreneurial samples to combat the inability to recover while encountering considerable stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Needs of an aging workforce and of those suffering from chronic disease or disability include the ability to improve working conditions so that they are adjusted to the residual abilities of the worker. One study found that such adjustments are more likely to be made by the self-employed and are less accessible to employees (Fleischmann et al 2018), which suggests that those workers with greater control over their own working conditions, and their working time, are more likely to successfully continue in the workforce after a diagnosis of chronic disease. Another study underlined the importance of adapting to the needs of those suffering from specific chronic illnesses, pointing out that incentives designed to promote return to work of those suffering from physical problems required different strategies than for those suffering from mental health problems (Vossen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If a worker experienced functional limitations due to a chronic disease, they may also report an adverse change in working conditions, while objectively no change occurred. 27 However, there are no differences in the amount of changes for the chronically ill population compared with the healthy population. Nevertheless, from the data it cannot be derived whether the changes took place due to the chronic disease or if they are independent of having a chronic disease.…”
Section: Discussionmentioning
confidence: 99%